2011
DOI: 10.1021/nl2019195
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Spectroscopy to Probe Reversibly Photoswitchable Azobenzene in Controlled Nanoscale Environments

Abstract: We apply in situ surface-enhanced Raman spectroscopy (SERS) to probe the reversible photoswitching of azobenzene-functionalized molecules inserted in self-assembled monolayers that serve as controlled nanoscale environments. Nanohole arrays are fabricated in Au thin films to enable SERS measurements associated with excitation of surface plasmons. A series of SERS spectra are recorded for azobenzene upon cycling exposure to UV (365 nm) and blue (450 nm) light. Experimental spectra match theoretical calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
165
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(167 citation statements)
references
References 80 publications
2
165
0
Order By: Relevance
“…Raman signals for different mole fractions of the molecules were also calculated to gain a better understanding of the switching efficiencies of molecules on the substrate. The analogous calculations for Azo1 (without the Au cluster) have been previously reported 37 and are used here in elucidating the role of the tether. Figure 2 shows the overlay of simulated Raman spectra of Azo2 molecules attached to Au 3 clusters as a convolution of various mole fractions of trans and cis isomers.…”
Section: Sectionmentioning
confidence: 90%
See 3 more Smart Citations
“…Raman signals for different mole fractions of the molecules were also calculated to gain a better understanding of the switching efficiencies of molecules on the substrate. The analogous calculations for Azo1 (without the Au cluster) have been previously reported 37 and are used here in elucidating the role of the tether. Figure 2 shows the overlay of simulated Raman spectra of Azo2 molecules attached to Au 3 clusters as a convolution of various mole fractions of trans and cis isomers.…”
Section: Sectionmentioning
confidence: 90%
“…The time constant from our study with Azo1 was found to be τ = 38 ± 13 min (unpublished results). 37 The reverse isomerization of Azo2 from cis to trans was also investigated by irradiating the sample with blue light (∼450 nm and power of 6 mW/cm 2 ), whereas Azo1 showed ∼90% reversibility in isomerization within 100 min of visible light illumination, 37 Azo2 did not exhibit complete reversibility, at least after 24 h of visible light illumination. Figure 6 shows a series of SERS spectra of the surface assembled with Azo2 under constant visible-light irradiation.…”
Section: Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a different chemical composition results in different vibrational modes specific to their chemical structure. The sharp peaks of metanil yellow at 1147 cm −1 and 1433 cm −1 , due to the N = N site are most definitive to its identification and quantification [67][68][69]. The 1631 cm −1 peak in turmeric spectrum is due to the carbonyl group.…”
Section: Detection Of Metanil Yellow Contamination In Turmeric Powdermentioning
confidence: 97%